Production and quality of forage of Sambucus nigra in living fences, high Colombian tropics - Navas-Panadero, Alexander (2021)
Introduction. Livestock feeding in Colombian high tropic livestock systems is based on monoculture grass grazing of low quality and low biomass during drought periods, which affects the productive performance of the animals. Objective. To evaluate the production and nutritional quality of forage of Sambucus nigra L., established as a silvopastoral live fence arrangement. Materials and methods. The research was carried out at the San Joaquin farm, located in Paipa, Colombia; the samplings were done between January 2019 and March 2020. In a live fence arrangement, a 226 m linear transect was selected, in which 17 trees were randomly selected. The green forage and dry matter production of the complete plant and its fractions (leaves and stems), the leaf - stem ratio and the nutritional quality (NIRS) of the complete plant and of each fraction were evaluated. A randomized design was carried out, descriptive statistics and analysis of non-parametric variance (Kruskal Wallis test) were performed for forage production and leaf-stem relationship, the data analysis was done using the Infostat¨ program. Results. The production of green forage and dry matter was 19, t km-1 year-1 and 3,9 t km-1 year-1, respectively. There were differences (p<0.0001) in nutritional quality, the leaves were of higher quality, the forage had a high crude protein content, metabolizable energy and digestibility, low percentage of neutral detergent fiber and acid detergent fiber, the leaf-stem ratio was 0.8: 1, although there were differences between samplings (p<0.0001). Conclusions. The living fences of S. nigra produced high production of edible biomass per kilometer per year, the forage of the complete plant and its fractions had good nutritional quality, crude protein, energy, and digestibility.